2021
DOI: 10.2147/cia.s329468
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Emergency Room Visits for Bleeding Complications Following Transurethral Procedures in the Treatment of Benign Prostatic Hyperplasia: A Retrospective Cohort Study

Abstract: Purpose Transurethral procedures, including transurethral resection of the prostate (TURP) and laser prostatectomy, are often linked to emergency room (ER) visits for postoperative bleeding. Although some studies have been conducted, the risk factors associated with these ER visits are not completely understood. This retrospective cohort study identified potential risk factors associated with ER visits for postoperative bleeding. Patients and Methods Preoperative assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
(29 reference statements)
0
4
0
1
Order By: Relevance
“…Furthermore, secondary hemorrhage can result in blood clot formation and deciduous scab aggregation, followingly leading to urinary tract obstruction and clot retention. [ 19 , 20 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, secondary hemorrhage can result in blood clot formation and deciduous scab aggregation, followingly leading to urinary tract obstruction and clot retention. [ 19 , 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, secondary hemorrhage can result in blood clot formation and deciduous scab aggregation, followingly leading to urinary tract obstruction and clot retention. [19,20] The CDC was usually used to classify the grade of complications within 90 days after the operation. [21] Our results showed that the patients with grade I, II, III complication in the HoLEP group were significantly lower than those in the TURP group, and the patients with grade I, II complication in the HoLEP group were significantly lower than those in the PKRP group.…”
Section: Itemsmentioning
confidence: 99%
“…De acuerdo con nuestra revisión, la RTUP es la cirugía con mayor índice de hemorragia en comparación con las otras técnicas transuretrales, sin embargo, la evidencia apoya que la B-RTUP tiene menores tasas de hemorragia que la M-RTUP. (19) Teniendo en cuenta que la literatura disponible indica que las técnicas endoscópicas conllevan un menor riesgo de sangrado y pueden ser beneficiosas en pacientes con anticoagulantes, se podría recomendar a este tipo de paciente el uso de HoLEP y la resección de la próstata con láser de tulio. Estos datos concuerdan con lo señalado por Rivera et al: HoLEP parece ser un procedimiento seguro y eficaz para los STUI relacionados con la HPB en pacientes que reciben terapia de anticoagulación y terapia antiplaquetaria.…”
Section: Discussionunclassified
“…PVP and ThuVARP are safer than M-TURP because blood transfusion, clot retention, hemoglobin decline, or transurethral resection syndrome is less likely to occur [ 35 ]. Our findings support changes in the surgical treatment of BPH from M-TURP to new laser methods [ 24 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high CCI score subgroup demonstrated increased HRs for ER visits within 90 days after surgery, whereas patients aged >80 years exhibited a significant risk of bleeding leading to rehospitalization. Our study suggested that laser surgery is safer than M-TURP for BPH because of reduced catheter time and risk of bleeding, even in patients receiving anticoagulant or antiplatelet therapy [ 23 , 35 , 40 ].…”
Section: Discussionmentioning
confidence: 99%